Ways of effectively using methods of interactive teaching of students at the architecture and construction university - Parmanov Jamshid Tagaymurodovich (Genius Journals, 2023)
In this article, we will look at every detail in today's modern world in the field of education with a modern eye. Including teaching students of each subject, in addition to its educational methodology, incorporating modern innovative technologies is one of the current issues. In this article, the author describes in detail the importance of physics in the world community and the use of innovative technologies in teaching this science to students.
Keywords: Technology; innovation; physics; pedagogical technologies